Hubungan Antara Sholat Tahajud dengan Tingkat Kecemasan pada Mahasiswa Universitas Islam Sultan Agung Semarang - Lolla Loviana Subakir; Wigyo Susanto; Dwi Heppy Rochmawati (Pusat Riset dan Inovasi Nasional, 2025)
Students are learners as well as part of society who are vulnerable to mental health disorders. This is due to the challenging academic journey, from the beginning of their studies to the final semester, in order to develop their ability to fulfill intellectual responsibilities. There are several simple methods that can be practiced independently to reduce anxiety symptoms, such as deep breathing techniques, avoiding alcohol consumption, sharing feelings with close ones, and strengthening spiritual connection with Allah SWT through performing Tahajud prayer. This study aims to analyze the relationship between Tahajud prayer and the level of anxiety among students at Sultan Agung Islamic University Semarang. The study employs a correlational design with a cross-sectional approach. Data were collected through questionnaires completed by 75 students using a total sampling technique. The results indicate that the majority of respondents, 65 students (86.7%), engage in Tahajud prayer regularly. However, most respondents, 50 students (66.7%), still experience high levels of anxiety. Statistical tests revealed a p-value of 0.000 (<0.05), demonstrating a significant relationship between Tahajud prayer and anxiety levels. Based on these findings, it can be concluded that there is a correlation between Tahajud prayer and students' anxiety levels. This study is expected to serve as a reference for future research and encourage students to utilize Tahajud prayer as a form of spiritual therapy in managing anxiety.